Faktor-faktor yang Memengaruhi Anticipatory Grief pada Family Caregiver Pasien yang Didiagnosis Kanker: Narrative Literature Review - Madani, I Gusti Ayu Winda; Suarya, Luh Made Karisma Sukmayanti (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2025)
Background: Family caregiver of patients with cancer often experience anticipatory grief (AG) when providing care. Although previous studies have explored AG in cancer contexts, most findings remain fragmented and focus only on isolated variable. Comprehensive reviews specifically examining the multifactorial determinants of AG among family caregivers of patient with cancer are limited. Objective: To synthesize recent empirical findings on the factors that influenced AG among family caregiver of cancer patients. Method: This study employed a literature review method following the PRISMA 2020 framework. Articles were searched from databases including Google Scholar, PubMed, and Sage Journals. The search terms were ("anticipatory grief" OR "pre-loss grief") AND ("caregiver" OR "family caregiver") AND ("cancer" OR "oncology"). From in total 21.066 articles, a screening was applied based on publication year (2021–2025), article type (empirical, quantitative research articles published in peer-reviewed journals included, while non-empirical papers excluded), full-text access, and topic relevance. Critical appraisal was conducted using JBI critical appraisal tool. Outcome: The review identified six factors which were then grouped into three categories. First category was risk factors, which consisted of caregiver burden, illness uncertainty, and post-traumatic stress symptoms. The second category was mediating factors, which included cognition and coping, and attachment. The third category was protective factors, which contained family functioning and resilience. Conclusion: This review identify that AG among family caregivers of patients with cancer influenced by three factors, i.e. risk factors, mediating factors, and protective factors.INTISARILatar belakang: Pengasuh keluarga dari pasien kanker sering mengalami anticipatory grief (AG) dalam melakukan perawatan. Meskipun beberapa penelitian sebelumnya telah membahas AG dalam konteks kanker, sebagian besar temuan masih terfragmentasi dan berfokus pada variabel tunggal. Tinjauan komprehensif yang secara khusus menelaah determinan multifaktorial AG pada pengasuh keluarga pasien kanker masih terbatas. Tujuan: Studi ini bertujuan untuk melakukan sintesis temuan empiris terkini mengenai faktor-faktor yang memengaruhi AG pada pengasuh keluarga pasien kanker. Metode: Penelitian ini menggunakan metode tinjauan literatur naratif berdasarkan pedoman PRISMA 2020. Pencarian artikel dilakukan melalui basis data Google Scholar, PubMed, dan Sage Journals. Kata kunci pencarian yang digunakan adalah ("anticipatory grief" OR "pre-loss grief") AND ("caregiver" OR "family caregiver") AND ("cancer" OR "oncology"). Dari total 21.066 artikel, dilakukan penyaringan berdasarkan tahun publikasi (2021–2025), tipe artikel (penelitian empiris kuantitatif yang diterbitkan di jurnal peer-reviewed, sedangkan artikel non-empiris dikecualikan), akses penuh, serta relevansi topik. Telaah kritis dilakukan menggunakan JBI critical appraisal tool. Hasil: Kajian ini mengidentifikasi enam faktor yang kemudian dikelompokkan menjadi tiga kategori, yaitu faktor risiko: beban pengasuh, ketidakpastian penyakit, dan gejala stres pascatrauma; faktor perantara: penilaian kognitif dan koping, kelekatan; faktor protektif: keberfungsian keluarga dan resiliensi. Simpulan: Kajian ini mengidentifikasi bahwa AG pada pengasuh keluarga pasien kanker dipengaruhi oleh faktor risiko, faktor perantara, dan faktor protektif.